Kualitas Tiga Jenis Madu Hutan Suku Baduy Kabupaten Lebak, Provinsi Banten - Rini Pujiarti; Azmi Amin; Agus Ngadianto; Ratih Madya Septiana; Brandon Aristo Verick Purba; Dwiko Budi Permadi (Fakultas Kehutanan Universitas Gadjah Mada, 2021)
This study aimed to determine the quality of defective honey, bitter honey, and sweet honey produced by the Baduy community. The bitter honey was collected from locations where nectar was sourced from calliandra, mahogany, sengon, and kamboja trees. The sweet honey was collected from locations where nectar was sourced from fruit trees such as bananas, sugar palm, durian, jackfruit, and rambutan. The defective honey is sweet honey that produces gas and therefore it is bubbly and considered to be damaged by the Baduy community. The research applied the criteria of the Indonesian National Standard SNI 8664 (2018) to test the quality of honey. The results showed that defective honey fulfills five criteria, i.e.: HMF testing, ash content, insoluble solids in water, acidity, smell, and taste. Bitter honey fulfilled four criteria, i.e., testing of ash content, water-insoluble solids, acidity, and moisture content. Sweet honey fulfilled seven criteria, i.e., the testing of ash content, sucrose, water-insoluble solids, acidity, moisture content, odor, and taste. All types of honey did not meet the criteria of diastase enzyme activity and reducing sugar levels. This could be due to conditions and storage time of honey before testing.